1998
DOI: 10.1093/hmg/7.13.2051
|View full text |Cite
|
Sign up to set email alerts
|

Mosaicism in sporadic neurofibromatosis 2 patients

Abstract: More than half of neurofibromatosis 2 (NF2) patients represent de novo mutations which could have occurred at either pre-zygotic or post-zygotic stages. A post-zygotic mutation can result in mosaicism. In four sporadic NF2 patients, we found NF2 mutations in only a portion of corresponding leukocytes. In two other sporadic patients, no mutations were found in leukocytes but constitutional NF2 mutations were suggested by identical mutations in different tumors from each patient. We screened leukocyte DNA from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
71
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 22 publications
6
71
1
1
Order By: Relevance
“…This is higher than previous estimates of 15-20%, 14 15 and corresponds to the difference in the mutation detection rate between people with new mutations (55%) and inherited cases (85%) in this study. Kluwe et al 14 reported direct molecular evidence of mosaicism in six NF2 patients with new mutations by finding mutational hits in blood in four people and in tumour material in two people. The difference in mutation detection rates between people with new mutations and inherited cases was 30%, a difference that they also attributed to mosaicism.…”
Section: Discussionmentioning
confidence: 99%
“…This is higher than previous estimates of 15-20%, 14 15 and corresponds to the difference in the mutation detection rate between people with new mutations (55%) and inherited cases (85%) in this study. Kluwe et al 14 reported direct molecular evidence of mosaicism in six NF2 patients with new mutations by finding mutational hits in blood in four people and in tumour material in two people. The difference in mutation detection rates between people with new mutations and inherited cases was 30%, a difference that they also attributed to mosaicism.…”
Section: Discussionmentioning
confidence: 99%
“…Wallace, personal communication). Review of the body of literature discussed in NF2 Constitutional Alterations section reveals that the majority of constitutional mutations in NF2 patients will be detected by careful exon scanning of blood samples (about 66%) Parry et al, 1996]); however, rates of pickup are clearly affected by disease severity (with low rates in mild patients and nearly 100% rates in very severe patients) and by founder status (with about 30% fewer founders detected than nonfounders) [Kluwe and Mautner, 1998]. In the 50% of patients who are founders, an additional 12% ] to 50% [Mohyuddin et al, 2003] of mutations will be found by exon scanning of tumors.…”
Section: Diagnostic Relevancementioning
confidence: 99%
“…10 Haplotype analysis of the patients, their children, and unaffected spouses as well as allelic loss analysis of the NF2 gene in tumors were performed using five microsatellite markers flanking or within the NF2 gene: CRYB2, D22S275, NF2CA3, D22S268, and D22S430. 12,13 Table 1, the clinical features of the four sporadic NF2 patients fulfill the updated NIH diagnostic criteria for NF2.…”
Section: Methodsmentioning
confidence: 99%
“…8 Recent findings suggest that 20% to 30% of sporadic NF2 patients may be mosaic. 9,10 In some mosaic cases, the leukocytes of the patients may not bear the mutations and, thus, the mutations cannot be found by screening their blood-DNA. Our previous study demonstrated that, in such cases, analysis of tumors can provide an additional opportunity to find constitutional mutations.…”
mentioning
confidence: 99%
See 1 more Smart Citation